LIFE, POLITICAL, PUBLIC AND LITERARY ACTIVITY OF SIMON PETLIURA IN MOSCOW IN 1911-1915 (130 - TO THE ANNIVERSARY OF BIRTH IS DEDICATED) - Ідзьо, В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The processes of establishment in the environment of the Ukrainian colony of city of Moscow of public, political, cultural magazine "Ukrainian Life" are examined in the floor. A basic accent is concentrated on the life, to political, public and literary activity, one of organizers of magazine Simon Petliura, activity of which in Moscow is analyzed from 1911 to 1915.